2022
DOI: 10.3390/healthcare10071192
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Korean Medicine Health Care Use for Functional Dyspepsia: Analysis of the Korea Health Panel Survey 2017

Abstract: Functional dyspepsia (FD) significantly reduces quality of life, and Korean medicine treatment, including herbal medicine, is frequently used in the clinical setting. We aimed to analyze the factors affecting Korean medicine health care (KMHC) use for FD. Data from the Korea Health Panel Survey 2017 were analyzed. Individuals aged >19 years who were diagnosed with FD and used outpatient care were included. Multiple logistic regression analyses were performed to investigate the association of predisposing, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 31 publications
(38 reference statements)
2
4
0
Order By: Relevance
“…Our study suggests that the characteristics observed among US adults attempting weight loss were more pronounced among the HM users than among the non-users. In addition, HM users demonstrated a significantly higher proportion of individuals holding private health insurance, a finding consistent with the characteristics of Korean medicine healthcare users, including HM, for patients with functional dyspepsia ( Lee et al, 2022b ).…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…Our study suggests that the characteristics observed among US adults attempting weight loss were more pronounced among the HM users than among the non-users. In addition, HM users demonstrated a significantly higher proportion of individuals holding private health insurance, a finding consistent with the characteristics of Korean medicine healthcare users, including HM, for patients with functional dyspepsia ( Lee et al, 2022b ).…”
Section: Discussionsupporting
confidence: 70%
“…Recently, policymaking according to evidence-based, real-world data (RWD) is increasing ( Cave et al, 2019 ; Kc et al, 2023 ), with RWD finding utility in the integrative medicine field for scrutinizing health outcomes, healthcare utilization, and associated factors ( Lee et al, 2022a ; Lee et al, 2022b ; Lee et al, 2023a ; Lee et al, 2023b ). By analyzing the characteristics and factors of HM users for weight loss, the demographics and variables of individuals who have unmet medical needs within conventional obesity treatment were identified.…”
Section: Introductionmentioning
confidence: 99%
“…Another study identified the factors that affected Korean medicine health care use by privately insured people and found that patients with more chronic diseases used Korean medicine services more ( 25 ). A study analyzing the factors that affected Korean medicine healthcare use for treating functional dyspepsia found that participants with private health insurance and who were frequently or constantly stressed used the Korean medicine healthcare system more ( 26 ). These studies have similar results to our study.…”
Section: Discussionmentioning
confidence: 99%
“…A different study identified factors related to Korean medicine health care use, including HM, acupuncture, and moxibustion, in privately insured adults ( 25 ). The latter study also identified factors related to Korean medicine health care use in adult patients with functional dyspepsia ( 26 ). Our study was different because we limited the populations to overweight and obese adolescents that used HM for weight loss and analyzed the factors separately according to sex.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this study analyzed the relations between control variables related to the use of KM and WM by the Andersen behavior model and then analyzed the relationship between KM use and WM use [ 14 , 15 ]. This model has been widely used to analyze factors that induce medical use in the research [ 16 ]. Accordingly, using Andersen’s behavioral model as a control variable, a complementary relationship analysis between KM use and WM use was conducted.…”
Section: Introductionmentioning
confidence: 99%